Leaf-Methanolic Extract of Pseudopanax arboreus (Araliaceae) (L. F. Phillipson) Reverses Amitriptyline-Induced Sexual Dysfunction in Male Rats - Egbe B. Besong; G. Ateufack; Smith B. Babiaka; Albert Kamanyi (Biochemistry Research International)
The people of the Bayangi tribe (Manyu Division) of Cameroon have used the leaves of Pseudopanax arboreus (Araliaceae) traditionally for decades as an aphrodisiac. In order to scientifically investigate this folk claim, we evaluated the effects of the leaf-aqueous extract of P. arboreus on the sexual behavior of normal male rats. The present study was designed to assess the effects of the leaf-methanolic extract of P. arboreus on amitriptyline-induced sexual dysfunction in male rats. Sexually impaired male rats were randomly divided into 4 groups of 8 rats each. Group 1 received 10 ml/kg distilled water, while group 2 was given 6 mg/kg Viagra. Groups 3 and 4 received 46.5 and 93 mg/kg of the leaf-methanolic extract, respectively. Female rats were made receptive by ovariectomy and subsequent hormonal treatment. Sexual behavior parameters were monitored on days 1, 7, 14, and 21 by pairing each male to a receptive female. The extract-treated rats registered significant decrease in mount latency (ML) and intromission latency (IL); nonsignificant increase in mount frequency (MF), intromission frequency (IF), and penile licking (PL); significant decrease in postejaculatory interval (PEI); contrasting effects in ejaculation latency (EL); and mean intromission interval (MII). Both doses of the extract also provoked a significant increase in relative weight of testes, but had no significant effect on the plasma hormonal profile. These findings are similar to those obtained with normal male rats and show that the leaf-methanolic extract of P. arboreus could constitute a potential solution to male sexual impairment.